Cholesterol Transbilayer Distribution and its Impact on Microdomains in the Mammalian Cell Plasma Membrane - Courtney, Kevin (Université d'Ottawa / University of Ottawa, 2017)
The plasma membrane (PM) of live cells has a striking phospholipid asymmetry between bilayer leaflets, yet the purpose of this fundamental structure remains elusive. It is also unknown whether and how this phospholipid asymmetry impacts on the lateral organization of the PM, such as microdomains or lipid rafts that are thought to facilitate specific protein-protein interactions. Here, we generated asymmetric giant unilamellar vesicles (GUVs) and found that microdomain formation is inhibited by outer leaflet very long acyl chain (24:0) sphingomyelin (SM), the primary sphingolipid species in mammalian cells. Interestingly, although cholesterol is believed to associate favourably with SM, molecular dynamic (MD) simulations of asymmetric membranes indicate a strong preference for cholesterol in the inner leaflet when 24:0 SM is in the outer leaflet, as well as, interdigitation of 24:0 SM acyl chain across the centre of the bilayer. We thus hypothesized that the outer leaflet-localized 24:0 SM interdigitates across the leaflets of the bilayer and facilitates cholesterol enrichment in the inner leaflet. Indeed, we obtained evidence that, in asymmetric unilamellar vesicles with 24:0 SM exclusively in the outer leaflet, 75-80% of cholesterol was partitioned into the inner leaflet, which was correlated with the disappearance of microdomains in GUVs. Importantly, in live cell PM, where 24:0 sphingolipids are the predominant species and exclusively in the outer leaflet, cholesterol was similarly enriched in the cytoplasmic leaflet. SM with shorter acyl chains such as 16:0, a minor species in mammalian cells, failed to generate cholesterol asymmetry and promoted microdomains in both symmetric and asymmetric GUVs. Furthermore, we generated live mammalian cells with either 16:0 or 24:0 SM and analyzed submicron domains in these cells, using density-dependent FRET of GPI-anchored proteins. Indeed, 16:0 SM cells are capable of forming submicron domains. The 24:0 SM cells, by contrast, are nearly devoid of submicron domains, as are unmodified control cells. Moreover, we silenced ceramide synthase 2 (CerS2), the enzyme that generates very long acyl chain sphingolipids. We found that silencing CerS2 alters diffusional properties of membrane proteins, consistent with enhanced microdomain formation. Together, our results establish a surprising and central role of very long acyl chain sphingolipids in regulating membrane lateral organization, including in the native plasma membrane, by creating cholesterol asymmetry. We propose that sphingolipid asymmetry functions to dynamically regulate microdomains in live cells.
Keywords: Transbilayer distribution; Membrane asymmetry; Cholesterol; Membrane microdomains